Fundamentals of Educational Language - Shilan Omar Hussein; Hawar Omar Faqi Amin (The Scientific Journal of Cihan University– Sulaimaniya, 2019)
The main purpose of the research entitled (Principles of Language in ,the Educational Curricula( the educational )its role and impact on the design and formulation of the education curriculum, under the light of theories of education, and it identifies how to learn. The field of study is determined by the relationship among educational linguistics, neurolinguistics, sociolinguistics, psycholinguistics, and so on, and the relationship of this science with education curricula. This study consists of an introduction, conclusion, resources, and the chapters will be as follows: Chapter One deals with ecology of lanugaue of education, and consists of three sections. Section deals with the purposes and analysis of the language of education; including the concept of educational linguistics, description of language of education, and the integration of language and education. Chapter Two deals with principles of language of education, including the basic principles, divided into four sections. Section one is about neurological bases of language, perception and brain techniques, neurolinguistics and learning first and second languages. The second topic involves the social bases of language, where it talks about education and subectivity, aspects of sociolinguitics, linguistic planning and language policy, and methods of conversation. The third section deals with the basis of psycholinguistics, where he teaches the language of the mind and behavior relationship, and the principle of linguistic knowledge overlap and thinking, language learning, first and second. Section IV contains the basis of linguistic knowledge of the language, and is divided into the function of language, the use of language in education, the classical language consolidated, the development of the student’s ability, and understanding of language learning, language and skill use, multilingualism, Dictation.